Use of an eHealth tool for exercise training and online contact in people with severe chronic obstructive pulmonary disease on long-term oxygen treatment: A feasibility study. (December 2020) - Sönnerfors, Pernilla; Wadell, Karin; Dohrn, Ing-Mari; Nyberg, André; Runold, Michael; Halvarsson, Alexandra
Technology developments and demand for flexibility in health care and in contact with the health care system are two factors leading to increased use of eHealth solutions. The use of eHealth has been shown to have positive effects in people with chronic obstructive pulmonary disease, but the full potential for this group needs to be explored. Therefore, the aim was to evaluate the feasibility of an eHealth tool used for exercise training and online contacts for people with severe chronic obstructive pulmonary disease. The 10-week intervention included an eHealth tool for exercise training in home environment and regular online contacts, as well as weekly e-rounds for health care professionals. Seven of the nine participants completed the study. The eHealth tool was found to be feasible for e-rounds, exercise training and online contacts. Participants could manage the tool and adhere to training; positive effects were shown, and no adverse events occurred. Technical functions need to be improved.